PERAN BAITUL MAAL WAT TAMWIL DALAM UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT PADA BMT AL-AMANAH KABUPATEN SINJAI - Santi Novita; Muhammad Nasri Katman; Muslihati (Program Studi Ekonomi Syariah, 2026)
Baitul Maal wat Tamwil (BMT) is an Islamic microfinance institution that plays a strategic role in mobilizing and distributing funds to the community through both social services and productive business financing. Its existence is expected to improve community welfare by empowering micro and small entrepreneurs. This study aims to analyze the role of BMT Al-Amanah in empowering the community's economy in Sinjai Regency and to identify the supporting and inhibiting factors affecting its implementation. This study employed a descriptive qualitative approach with economic and sociological perspectives. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that BMT Al-Amanah contributes to community economic empowerment by providing business capital financing, financial management assistance, and business promotion guidance. Supporting factors include the availability of financing funds and strong relationships with customers, while the main inhibiting factor is customers' limited availability to participate in mentoring activities. Therefore, BMT Al-Amanah has made a positive contribution to community economic empowerment through sustainable financing and business development programs